Advancement in ophthalmic services in Nepal through sharing of knowledge, skills and experience - Tegelberg, U F (Nepalese Journal of Ophthalmology, 2015)
I first came to beautiful Nepal in 1989 with a group of friends from The Netherlands to try to help out our Nepali colleagues in Nepal’s need for ophthalmic assistance. We were appalled to find that the rural people of Nepal had practically no access to ophthalmic services. People were going around half-blind or towards being totally blind.